Cerebral oedema is rare in acute‐on‐chronic liver failure patients presenting with high‐grade hepatic encephalopathy. (12th July 2013) - Joshi, Deepak; O'Grady, John; Patel, Amit; Shawcross, Debbie; Connor, Steven; Deasy, Neil; Willars, Chris; Bernal, William; Wendon, Julia; Auzinger, Georg
Abstract Background & Aims Acute‐on‐chronic liver failure (ACLF) has a rapidly progressive disease course associated with significant mortality. The prevalence of clinically significant cerebral oedema in ACLF is unknown. Methods We aimed to describe the prevalence of cerebral oedema in a cohort of ACLF adult (>18 years). We identified patients admitted to a single, specialist intensive care unit between January 2005 and January 2011 with high‐grade hepatic encephalopathy (≥3) and a clinical picture of either ACLF or chronic liver disease (CLD). Patients who had undergone cranial CT imaging were identified and their imaging reviewed. The ACLF and CLD groups were compared. Results One thousand and eight patients with CLD were admitted. One hundred and seventy‐three patients (110 male) underwent neuroimaging. Eighty‐one (48 male) fulfilled criteria for ACLF. Variceal bleeding (30%) and sepsis (31%) were the most frequent precipitants of ACLF. Of those with neuroimaging from the total cohort, 30% of CT scans were normal, 30% demonstrated increased cerebral atrophy for age, 17% small vessel disease and 16% intracranial haemorrhage (ICH). Cerebral oedema was seen in three patients with ACLF only. An increased prevalence of ICH was observed in the ACLF group (23% vs. 9%, P = 0.008). Conclusion The prevalence of clinically relevant cerebral oedema was low (4%) but fatal. Death was attributable to tonsillar herniation. An increased prevalence of ICH was seen in ACLF patients and remains an important differential.